FACTOR DE DESCONTAMINACION EN LA PRECIPITACION QUIMICA DEL CESIO-137 - Mallaupoma Gutiérrez y Cols., Mario (2019)
The main objective of the present paper is the determining of the decontamination factor in the chemical separation of caesium-137. The separation of this radioisotope is is very important because it could pose risks to human health and the environment. It was noted that the higher values of decontamination factor was achieved with the addition of nickel sulphate 0.7 M to a solution of potassium ferrocyanide 0.5 M. The results show the advantage resulting from the addition of bentonyte because it increases the surface for the adsorption of caesium 137. Similarly it is noted that the pH has an important role during the respective precipitation.